UPAYA UNI EROPA DALAM MENYELESAIKAN MASALAH PERBATASAN IRLANDIA PASCA-REFERENDUM BREXIT - Ruddin, Muhaskha Haspul; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
This research discusses the efforts and actions taken by the European Union in solving the Irish Border problems after the UK left the European Union or Brexit. The Brexit Referendum left problems related to cross-border interaction between the Republic of Ireland which is a member of the European Union and Northern Ireland which is in the territory of the United Kingdom. The Irish border is the only land border that the United Kingdom has. Efforts made by the European Union as a supranational organization that oversees the European region are related to policy making and regulation establishment as a solution. This research is based on the theory of the Role of International Organizations. The level of analysis of this research focuses on the level of state analysis which lies in how the state plays a role in responding to and taking foreign policy. Data collection was carried out using the document analysis method which was reviewed through references from books, journals, websites, and other references relevant to this research study. The results of this research indicate that the European Union's efforts to resolve the issue of the Irish Border after the Brexit Referendum is by implementing the Protocol of Ireland / Northern Ireland which contains regulations and policies agreed upon by the United Kingdom with the European Union and the Republic of Ireland while maintaining the principles of the Good Friday Agreement or the Belfast Agreement. Efforts to implement the Protocol of Ireland / Northern Ireland as a solution to the Irish Border problem began with a Backstop Policy proposal which found no solution. In order to maintain regulatory changes from the implementation of the Protocol of Ireland / Northern Ireland, the European Union continues to monitor and evaluate the implementation of the protocol on the Irish Border. Keywords: European Union, Brexit, Irish Border, Effort, Policy